1976
DOI: 10.3177/jnsv.22.201
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental studies on physiological and pharmacological actions of L-ascorbate 2-sulfate. I. On the hypolipidemic effects.

Abstract: SummaryThe effects of L-ascorbate 2-sulfate (AAS) on the lipid metabolism were examined in Triton-induced hyperlipemic mice, hyper cholesterolemic and normal rats, the following results being obtained. 1) In Triton-induced hyperlipemic mice, AAS (300mg/kg) significantly decreased the serum cholesterol level, while L-ascorbate (AA, 175mg/kg) was found ineffective.2) In hypercholesterolemic rats fed 0.5% cholester ol diet, the consecutive administration of AAS decreased the level of serum cholesterol and liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Analyses of lipids and AA: Analysis of lipids in serum and liver were carried out as described in the previous papers (6,7). AA in various organs was extracted by homo genization with 1.4N acetic acid in 6 % metaphosphoric acid and centrifuging at 3,000 rpm for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of lipids and AA: Analysis of lipids in serum and liver were carried out as described in the previous papers (6,7). AA in various organs was extracted by homo genization with 1.4N acetic acid in 6 % metaphosphoric acid and centrifuging at 3,000 rpm for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…We reported in previous papers that AAS exerts lipid lowering effects in experimental hyperlipidemia with mice, rats and rabbits, and prevents development of atherosclerosis (6,7). In an attempt to dissociate the effect of AAS from that of L-ascorbic acid (AA), the present study of AAS on lipid metabolism has been carried out in guinea pigs which do not to biosynthesize AA in vivo.…”
Section: L-ascorbatementioning
confidence: 99%
“…It was reported that AAS has hypolipidemic effects in normal rats in a dose of 250mg/kg, in cholesterol-fed rats and rabbits in doses of 150 and 300mg/kg, and in cholesterol-fed guinea pigs at a dose of 300mg/kg, respectively (4)(5)(6). In this experiments, AAS was effective at a dose of 300 mg/kg on fatty liver and/or hyperlipidemia induced by various treatments (Tables 2 and 5).…”
Section: Discussionmentioning
confidence: 63%
“…Determinations of lipids in serum and liver and AA in various organs were carried out as described in previous papers (4,6). The results were statistically analyzed using Student's t-test.…”
mentioning
confidence: 99%
“…However, these levels were considerably altered over the 5-day injection period with a combination of cholesterol and ergocalciferol. While the significant hyper cholesterolemia (Table 3) was not as great as that observed after several months on a high-cholesterol diet, the increased triglycerides (Table 4) and decreased % HDL (Table 5) were of magnitudes consistent with the development of athero sclerosis (16). Increased % LDL, which occurs concomitant with decreased % HDL in rabbits (17) may be atherogenic by invasion of the endothelial wall (18).…”
Section: Discussionmentioning
confidence: 79%